2021
DOI: 10.1007/s00296-021-05010-2
|View full text |Cite
|
Sign up to set email alerts
|

YouTube as a source of information on COVID-19 vaccination in rheumatic diseases

Abstract: As the most well-known and popular video-sharing platform around the world, YouTube is an influential tool for the dissemination of health-related information. In addition, considering the increase in obtaining information from internet-based sources in pandemic conditions, YouTube has become more important in the presentation of information related to COVID-19. Therefore, the aim of this study was to evaluate videos related to COVID-19 vaccination in rheumatic diseases (RD) on YouTube. In this descriptive stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 26 publications
0
13
0
3
Order By: Relevance
“…We conducted our study on YouTube because it is the leading video-sharing platform. Although there have been several studies on YouTube videos about COVID-19 and long COVID-19, to the best of our knowledge, there has been no study on post-COVID pain, an important symptom of the disease that has a negative impact on the quality of life ( Chan et al, 2021 ; Jacques et al, 2022 ; Kocyigit & Akyol, 2021 ). Considering that pain is a major cause of disability and can last for up to 11 weeks after infection, disrupts patients’ quality of life, and causes them to stay home during that period and search for disease-related information online, it is important to screen YouTube videos on post-COVID pain and evaluate their reliability and quality ( Jacques et al, 2022 , Şahin et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We conducted our study on YouTube because it is the leading video-sharing platform. Although there have been several studies on YouTube videos about COVID-19 and long COVID-19, to the best of our knowledge, there has been no study on post-COVID pain, an important symptom of the disease that has a negative impact on the quality of life ( Chan et al, 2021 ; Jacques et al, 2022 ; Kocyigit & Akyol, 2021 ). Considering that pain is a major cause of disability and can last for up to 11 weeks after infection, disrupts patients’ quality of life, and causes them to stay home during that period and search for disease-related information online, it is important to screen YouTube videos on post-COVID pain and evaluate their reliability and quality ( Jacques et al, 2022 , Şahin et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that a significant number of internet users only view search results listed on the first three pages (60 videos in total, 20 on each page) ( Onder & Zengin, 2021 ; Rittberg, Dissanayake & Katz, 2016 ). Although YouTube has switched from page ranking to continuous listing, we based our search on the method used in similar studies and identified 60 videos for each search term ( Kocyigit & Akyol, 2021 ; Tolu et al, 2018 ). Video listing was done based on the number of views to evaluate videos with the greatest impact on society.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reliability of the video content and the quality of the videos are important issues at this point. Despite all its positive features, there are concerns about users accessing high-quality information on YouTube [11]. YouTube contains both high-quality informational videos and misleading videos [12].…”
Section: Introductionmentioning
confidence: 99%